Estabelecimento de Brachiaria humidicola cv. comum sob adubação fosfatada em solo do Estado Amazonas - (:unkn) unknown (Universidade Federal do Amazonas, 2016)
Objective was to evaluate the effect of phosphate levels in the growth and development of Brachiaria humidicola cv. Comum, phosphorus availability by different extractors and morphogenetic and structural characteristics. was conducted at the Federal University of Amazonas (Amazonas University), study Oxisoil (LA) and Gleysol Haplic (GX), samples of 100 grams of soil from the experimental units were collected to determine the availability by Mehlich-1, Mehlich-3 and resin exchange anions. To estimate the levels of maximum physical efficiency (MEF) and maximum economic efficiency (MEE), and the MEE was possible to establish the critical levels of phosphorus in soil and plant. The study was conducted to standardization of the aerial part, and 45 days after the standardization was made the first cut evaluation (C1) and 90 days the second cut 2 (C2). All the collected aerial plant was separated into its components: stem + sheath and leaf laminae, which were dried at 55ºC and weighed separately followed. The experimental design was randomized blocks with seven increasing doses phosphate with five repetitions, totaling 35 experimental units for each soil. Analyses of variance and regression were performed using STATISTICA Application 13 program, adopting the probalilidade of 5 and 1% significance. With results observed effect of phosphorus fertilization in all components of the forage, reflecting positively on dry matter of the aerial part (MSPA) in both the courts and the sum of these, for both soils. Phosphorus recuperation applied was higher by Mehlich-3 extractor in both soils. Critical levels of phosphorus in soil and plant are close to those cited by the literature. phosphate increasing levels promoting effect on the morphogenetic and structural characteristics evaluated. It is concluded that the phosphorus requirement is highest to 75 days after emergence and all extractors were efficient in predicting the availability of phosphorus in the soil, the resin being the extractor with the highest correlation with the phosphorus content in the shoot.
Keywords: Extrator de fósforo; Morfogênese; Nível crítico no solo; Nível crítico na planta; CIÊNCIAS AGRÁRIAS: AGRONOMIA: CIÊNCIA DO SOLO